Theoretical Study of Upper Critical Magnetic Field (HC2) in Multiband Iron Based Superconductors - Tsadik Kidanemariam; Gebregziabher Kahsay (Advances in Condensed Matter Physics)
This research work focuses on the theoretical investigation of the upper critical magnetic field, HC2; Ginzburg-Landau coherence length, ξGL(T); and Ginzburg-Landau penetration depth, λGL(T), for the two-band iron based superconductors BaFe2(As1-xPx)2, NdO1-xFxFeAs, and LiFeAs. By employing the phenomenological Ginzburg-Landau (GL) equation for the two-band superconductors BaFe2(As1-xPx)2, NdO1-xFxFeAs, and LiFeAs, we obtained expressions for the upper critical magnetic field, HC2; GL coherence length, ξGL; and GL penetration depth, λGL, as a function of temperature and the angular dependency of upper critical magnetic field. By using the experimental values in the obtained expressions, phase diagrams of the upper critical magnetic field parallel, HC2∥c, and perpendicular, HC2⊥c, to the symmetry axis (c-direction) versus temperature are plotted. We also plotted the phase diagrams of the upper critical magnetic field, HC2 versus the angle θ. Similarly, the phase diagrams of the GL coherence length, ξGL, and GL penetration depth, λGL, parallel and perpendicular to the symmetry axis versus temperature are drawn for the superconductors mentioned above. Our findings are in agreement with experimental observations.